Autism Symptoms in Children and Young Adults With Fragile X Syndrome, Angelman Syndrome, Tuberous Sclerosis Complex, and Neurofibromatosis Type 1: A Cross-Syndrome Comparison - Lubbers, Kyra; Stijl, Eefje M.; Dierckx, Bram; Hagenaar, Doesjka A.; ten Hoopen, Leontine W.; Legerstee, Jeroen S.; de Nijs, Pieter F. A.; Rietman, André B.; Greaves-Lord, Kirstin; Hillegers, Manon H. J.; Dieleman, Gwendolyn C.; Mous, Sabine E.; et al. (Frontiers in Psychiatry, 2022)
Objective: The etiology of autism spectrum disorder (ASD) remains unclear, due to genetic heterogeneity and heterogeneity in symptoms across individuals. This study compares ASD symptomatology between monogenetic syndromes with a high ASD prevalence, in order to reveal syndrome specific vulnerabilities and to clarify how genetic variations affect ASD symptom presentation. Methods: We assessed ASD symptom severity in children and young adults (aged 0-28 years) with Fragile X Syndrome (FXS, n=60), Angelman Syndrome (AS, n=91), Neurofibromatosis Type 1 (NF1, n=279) and Tuberous Sclerosis Complex (TSC, n=110), using the Autism Diagnostic Observation Schedule and Social Responsiveness Scale. Assessments were part of routine clinical care at the ENCORE expertise center in Rotterdam, the Netherlands. First, we compared the syndrome groups on the ASD classification prevalence and ASD severity scores. Then, we compared individuals in our syndrome groups with an ASD classification to a non-syndromic ASD group (nsASD, n=335), on both ASD severity scores and ASD symptom profiles. Severity scores were compared using MANCOVAs with IQ and gender as covariates. Results: Overall, ASD severity scores were highest for the FXS group and lowest for the NF1 group. Compared to nsASD, individuals with an ASD classification in our syndrome groups showed less problems on the instruments’ social domains. We found a relative strength in the AS group on the social cognition, communication and motivation domains and a relative challenge in creativity; a relative strength of the NF1 group on the restricted interests and repetitive behavior scale; and a relative challenge in the FXS and TSC groups on the restricted interests and repetitive behavior domain. Conclusion: The syndrome-specific strengths and challenges we found provide a frame of reference to evaluate an individual’s symptoms relative to the larger syndromic population and to guide treatment decisions. Our findings support the need for personalized care and a dimensional, symptom-based diagnostic approach, in contrast to a dichotomous ASD diagnosis used as a prerequisite for access to healthcare services. Similarities in ASD symptom profiles between AS and FXS, and between NF1 and TSC may reflect similarities in their neurobiology. Deep phenotyping studies are required to link neurobiological markers to ASD symptomatology.